Development and validation of the Malay version of the perception and awareness of cyberbullying questionnaire among the Malaysian parents and caregivers - Kumaran, Thenmoli Chandira (2023)
Background: Cyberbullying is becoming a common and alarming issue among children and adolescents. This situation must be given attention as the victims are repeatedly threatened, harassed, humiliated, embarrassed, or likewise targeted by the perpetrator. This can be done on the basis includes developing awareness among the parents and caregivers. However, so far, there is no validated questionnaire available in the Malay language to assess the perception and awareness of cyberbullying among parents and caregivers in Malaysia. Therefore, there is a need to develop and validate a questionnaire in the Malay language to measure their Perceptions and Awareness of Cyberbullying. Objective: This study is to develop a questionnaire in the Malay language to assess the Perceptions and Awareness of Cyberbullying among parents in Malaysia and to determine its validity and reliability. Method: A cross-sectional study involving 270 participants from 20 to 60 years old was conducted from December 2020 to November 2022 via an online questionnaire form. A Malay Version of The Perceptions and Awareness of Cyberbullying Questionnaire among parents was developed through three phases namely item development, scale development and scale evaluation. It was named as soal selidik Kesedaran dan Persepsi buli siber dalam kalangan ibu bapa (KEPS - I). The Content and Face Validation Index were done to ensure KEPS - I has good face and content validity. The finalized version of KEPS - I was harmonized and pre-tested on 30 participants. Study participants then completed the socio-demographic questionnaire and KEPS-I questionnaire. Data were analyzed using SPSS version 26 for construct validity by performing exploratory factor analysis (EFA), construct reliability, and test-retest reliability. Result: In this study, the initial scale was developed with six factors and 48 items. While the final model of KEPS-I comprises five factors with 34 items after undergoing the EFA. A final question (Question 34) is an open-answer question that was incorporated as the last question. The findings revealed acceptable factor loading, which is more than 0.4, overall Cronbach's alpha is good (0.894 - 0.939), yet poor test-retest reliability (ICC = 0.293). Conclusion: The study revealed that KEPS - I with five factors and 34 items has good psychometric properties. The scale is valid and reliable to measure the Perceptions and Awareness of Cyberbully among parents in Malaysia, although it showed poor stability.